Linguistic and translation aspects of political correctness in media texts - Kovalova, Olena; Nikitenko, Olga (My University, 2022)
Due to globalisationand forming of international and intercultural relations, the role of political correctness as a guarantor of successful communication between different social groups is growing. Wide use of this lexical layer in media texts, direct influence of politically correct units on social relations through mass media and the insufficient number of studies related to the translation of French politically correct terminology in media discourse determine the relevance of the study. The relevance of the study is due to the factors that there is no single approach to the analysis of political correctness in the scientific literature, and there is no single definition of "political correctness" in spite of the fact that it is firmly established in many languages. Moreover, although political correctness as a tool of communicative strategy of behavior is aimed at avoiding social aggravation and achieving a conflict-free atmosphere in society, provokes a lot of heated debates, which fact does not meet its main purpose and only emphasizes the contradictions.

Стаття спрямована на пошук та аналіз засобів передачі семантичного змісту політкоректних лексичних одиниць, які функціонують у медіатекстах у процесі їх перекладу українською мовою. Об’єктом дослідження є соціальні дискурсивні маркери політкоректності в медіатексті. Предметом дослідження є засоби перекладу політкоректних одиниць у медіатекстах українською мовою. Актуальність дослідження обумовлена тим, що в науковій літературі немає єдиного підходу до аналізу політкоректності, а також немає єдиного визначення поняття «політична коректність», незважаючи на те, що воно міцно закріпилося в багатьох мовах. Більше того, хоча політкоректність як інструмент комунікативної стратегії поведінки спрямована на уникнення соціального загострення та досягнення безконфліктної атмосфери в суспільстві, викликає багато гострих дискусій, що не відповідає своїй основній меті і лише підкреслює суперечності. Після аналізу медіатекстів були зроблені висновки про основні методи перекладу політкоректних одиниць.
Keywords: кафедра ділової іноземної мови та міжнародної комунікації; media text; political correctness; ideology; social-cultural aspect; translation transformation; медіатекст; політкоректність; ідеологія; соціально-культурний аспект; перекладацька трансформація